Intensification of the preparation process of suspencions and paints used in foundry production - Yu. P. Ledjan; P. Yu. Ledjan (Литьë и металлургия)
А new way of preparation of suspensions used in foundry production is worked out. New technological equipment is created and implemented allowing to sharply reduce suspension preparation time and to substantially decrease energy capacity of the process.